Answers

The Brainliest Answer!
2014-05-28T17:12:26+05:30
1+x+x^2+..+x^7+x^9-x=1+x^2+x^3+,,x^7+x^9 \\ =1+x^2+x^3(1+x^2)+x^4(1+x^2)+x^7(1+x^2) \\ =(1+x^2)(1+x^3+x^4+x^7)=(1+x^2)(1+x^3)(1+x^4)
((1+x^2)(1+x^3)(1+x^4))^{11}=(1+x^2)^{11}(1+x^3)^{11}(1+x^4)^{11}
So for coefficent of x⁷ 
     x^4 from  (1+x⁴)¹¹ and x³ from (1+x³)¹¹
    x⁴ from (1+x²)¹¹ and x³ from (1+x³)¹¹   
  =C^{11}_{1}C^{11}_{1}+C^{11}_{2}C^{11}_{1}=11(11)+(11*5)11=726
2 5 2
  • Brainly User
2014-05-29T10:24:49+05:30


   

hope it helped u if yes mark as the best

0
sorry but the answer didnt came so please anyone delete it